(untitled) (Atti del Sodalizio Glottologico Milanese, 2014)
Several basic-lexicon etymologies, with regular sound correspondences, suggest Hurro-Urartian (HU) might be derived from (or related to) Proto-Indo-European (PIE). Preliminary evidence suggests North-Caucasian (NC) languages might also be related to PIE – in particular, to Iranian languages and Armenian. KEYWORDS: reconstruction, Proto-Indo-European, Hurro-Urartian, North-Caucasian, etymology